Consumer Protection Policy for Conducting E-Commerce Transactions in Indonesia - Fatria Khairo (Universitas Sultan Ageng Tirtayasa, 2022)
A few decades ago, the internet was only known by a handful of people who did have an interest in the world of technology, especially computers. However, with the increasing years and the times, people's interest in the internet is growing rapidly, even the internet has become an inseparable part of their lives. Now the internet is not only entertainment and information; it has even been used as a medium of business and trade known as Electronic Commerce (E-Commerce). E-Commerce is buying and selling carried out via the internet, which can benefit consumers. Still, on the other hand, sometimes it is detrimental to consumers because they often do not get the protection that provides certainty in a dispute. In the E-commerce business transaction, which is a characteristic of business to business transactions where business actors conduct transactions with fellow entrepreneurs, business-to-consumer transactions are carried out by business actors with consumers themselves. The benefits of E-Commerce transactions for consumers, consumers can make transactions for 24 hours without leaving the house and do not require transportation for selling costs. Protection of E-Commerce consumers is regulated in Law Number 8 of 1999 concerning consumer protection for online transactions or E-commerce. In the Trade Law, the regulated E-commerce trading system stipulates that every person or business entity that trades goods or services must provide complete and correct data and information.